Pragmatic recommendations for infection prevention and control practices for healthcare facilities in low- and middle-income countries during the COVID-19 pandemic - Cobb, N; Papali, A; Pisani, L; Schultz, MJ; Ferreira, JC (American Society of Tropical Medicine and Hygiene, 2021)
Infection prevention and control (IPC) strategies are key in preventing nosocomial transmission of COVID-19. Several commonly used IPC practices are resource-intensive and may be challenging to implement in resource-constrained settings. An international group of healthcare professionals from or with experience in low- and middle-income countries (LMICs) searched the literature for relevant evidence. We report on a set of pragmatic recommendations for hospital-based IPC practices in resource-constrained settings of LMICs. For cases of confirmed or suspected COVID-19, we suggest that patients be placed in a single isolation room, whenever possible. When single isolation rooms are unavailable or limited, we recommend cohorting patients with COVID-19 on dedicated wards or in dedicated hospitals. We also recommend that cases of suspected COVID-19 be cohorted separately from those with confirmed disease, whenever possible, to minimize the risk of patient-to-patient transmission in settings where confirmatory testing may be limited. We suggest that healthcare workers be designated to care exclusively for patients with COVID-19, whenever possible, as another approach to minimize nosocomial spread. This approach may also be beneficial in conserving limited supplies of reusable personal protective equipment (PPE). We recommend that visitors be restricted for patients with COVID-19. In settings where family members or visitors are necessary for caregiving, we recommend that the appropriate PPE be used by visitors. We also recommend that education regarding hand hygiene and donning/doffing procedures for PPE be provided. Last, we suggest that all visitors be screened for symptoms before visitation and that visitor logs be maintained.